Application of oil-degrading agents consisted of thermophilic Bacillus subtilis and Bacillus glycinifermentans in food waste - Wang, Wenfan (Environmental technology, 2024)
This work aims to investigate the effective removal of oil in food waste (FW). Two bacteria, Bacillus subtilis and Bacillus glycinifermentans, were obtained under high temperature conditions and named YZQ-2 and YZQ-5, respectively. The oil degradation rate of two bacteria was explored under different pH value, temperature, and NaCl concentration. In addition, the lipase and emulsifying activity were evaluated. The maximum oil degradation rate was 83.41 ± 0.86% and the maximum lipase activity reached 89.73 ± 20.89 U L-1 with YZQ-2. The fermentation broth of YZQ-2 displayed exceptional emulsification activity. Subsequently, YZQ-2 and YZQ-5 were added to aerobic FW composting. The moisture content of the compost treated with inoculated strains decreased at a faster rate during the first three days of composting. The microbial quantity increased rapidly in the first three days, and the oil degradation rate reached 39.96% after five days. Due to the excellent adaptability to high temperature and ability to degrade oil, strains YZQ-2 and YZQ-5 exhibit superior potential for various applications